Liberia : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This Selected Issues paper discusses initiatives to promote export diversification and growth in Liberia. Liberia's exports have been very concentrated in the past, but some progress in export diversification has been made in recent years, mostly in the enclave sectors. The government has launched the Liberia Agricultural Transformation Agenda (LATA) to support diversification and transformation. LATA strives to build up the agricultural sector as well as adopt a supportive industrial policy. Improving business climate and external competitiveness could play an important role in increasing export diversification in Liberia. Efficiency could also be increased through better access to markets and technology, cheaper imported inputs, as well as more competition with imports.